FOLFIRINOX for locally advanced pancreatic cancer: a systematic review and patient-level meta-analysis. Issue 6 (June 2016) - Suker, Mustafa; Beumer, Berend R; Sadot, Eran; Marthey, Lysiane; Faris, Jason E; Mellon, Eric A; El-Rayes, Bassel F; Wang-Gillam, Andrea; Lacy, Jill; Hosein, Peter J; Moorcraft, Sing Yu; Conroy, Thierry; et al.
Summary: Background: 35% of patients with pancreatic cancer have unresectable locally advanced disease at diagnosis. Several studies have examined systemic chemotherapy with FOLFIRINOX (leucovorin and fluorouracil plus irinotecan and oxaliplatin) in patients with locally advanced pancreatic cancer. We aimed to assess the effectiveness of FOLFIRINOX as first-line treatment in this patient population. Methods: We systematically searched Embase, MEDLINE (OvidSP), Web of Science, Scopus, PubMed Publisher, Cochrane, and Google Scholar from July 1, 1994, to July 2, 2015, for studies of treatment-naive patients of any age who received FOLFIRINOX as first-line treatment of locally advanced pancreatic cancer. Our primary outcome was overall survival. Secondary outcomes were progression-free survival; rates of grade 3 or 4 adverse events; and the proportion of patients who underwent radiotherapy or chemoradiotherapy, surgical resection after FOLFIRINOX, and R0 resection. We evaluated survival outcomes with the Kaplan–Meier method with patient-level data. Grade 3 or 4 adverse events, and the proportion of patients who underwent subsequent radiotherapy or chemoradiotherapy or resection, were pooled in a random-effects model. Findings: We included 13 studies comprising 689 patients, of whom 355 (52%) patients had locally advanced pancreatic cancer. 11 studies, comprising 315 patients with locally advanced disease, reported survival outcomes and were eligible for patient-level meta-analysis. Median overall survival from the start of FOLFIRINOX ranged from 10·0 months (95% CI 4·0–16·0) to 32·7 months (23·1–42·3) across studies with a pooled patient-level median overall survival of 24·2 months (95% CI 21·7–26·8). Median progression-free survival ranged from 3·0 months (95% CI not calculable) to 20·4 months (6·5–34·3) across studies with a patient-level median progression-free survival of 15·0 months (95% 13·8–16·2). In ten studies comprising 490 patients, 296 grade 3 or 4 adverse events were reported (60·4 events per 100 patients). No deaths were attributed to FOLFIRINOX toxicity. The proportion of patients who underwent radiotherapy or chemoradiotherapy ranged from 31% to 100% across studies. In eight studies, 154 (57%) of 271 patients received radiotherapy or chemoradiotherapy after FOLFIRINOX. The pooled proportion of patients who received any radiotherapy treatment was 63·5% (95% CI 43·3–81·6, I 2 90%). The proportion of patients who underwent surgical resection for locally advanced pancreatic cancer ranged from 0% to 43%. The proportion of patients who had R0 resection of those who underwent resection ranged from 50% to 100% across studies. In 12 studies, 91 (28%) of 325 patients underwent resection after FOLFIRINOX. The pooled proportion of patients who had resection was 25·9% (95% CI 20·2–31·9, I 2 24%). R0 resection was reported in 60 (74%) of 81 patients. The pooled proportion of patients who had R0 resection was 78·4% (95% CI 60·2–92·2, I 2 64%). Interpretation: Patients with locally advanced pancreatic cancer treated with FOLFIRINOX had a median overall survival of 24·2 months—longer than that reported with gemcitabine (6–13 months). Future research should assess these promising results in a randomised controlled trial, and should establish which patients might benefit from radiotherapy or chemoradiotherapy or resection after FOLFIRINOX. Funding: None.